Pressure drop coefficient of laminar newtonian flow in axisymmetric sudden expansions - Oliveira, Paulo J. (2010)
Made available in DSpace on 2010-04-28T10:07:17Z (GMT). No. of bitstreams: 1 ri3.pdf: 981581 bytes, checksum: 72b94f040afb9adafbc4147fd07f8c84 (MD5)